Fragmentation, conflict, and competition: Islamist anti-civilian violence in sub-Saharan Africa - Dowd, Caitriona (Terrorism and political violence, 2019)
In spite of the shared high profile of recent Islamist attacks on civilians in sub-Saharan Africa, patterns of anti-civilian violence differ across and within violent Islamist groups, and the countries in which they are active. This research seeks to explain this variation by situating Islamist violence within the sub-national spaces in which such groups operate, and the wider conflict environment in which they choose to use, or limit the use of, anti-civilian violence. Drawing on data from the Armed Conflict Location & Event Dataset, the research finds that violent Islamist groups are more likely to target civilians where they are the most active conflict agent, even when other conflict agents are active in the same spaces; but less likely to do so when they are relatively weak and in competition with other non-state armed groups. Anti-civilian violence is thus deployed strategically by violent Islamist groups, while its function as a signalling or retributive policing tool depends on the relative strength of groups in relation to actors in the wider conflict arena.